2021
DOI: 10.1002/tox.23396
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor‐α36 is involved in diallyl sulfide‐induced inhibition of malignant growth of HepG2 and Huh7 hepatocellular carcinoma cells

Abstract: Hepatocellular carcinoma (HCC) is a highly malignant disease that currently lacks effective treatment. Epidemiological studies have suggested the preventive role of raw garlic intake in different tumors, such as HCC. Although diallyl sulfide (DAS), the main component of garlic extracts, has been reported to inhibit the growth of HCC cells, the underlying mechanism remains elusive. This study aimed to investigate the inhibitory effect of DAS on the growth of HepG2 and Huh7 hepatocellular carcinoma cells and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Western blot analysis was performed as described previously 31–33 . Total protein from treated HEC1B and KLE cells was extracted using ice‐cold lysis buffer (Beyotime, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blot analysis was performed as described previously 31–33 . Total protein from treated HEC1B and KLE cells was extracted using ice‐cold lysis buffer (Beyotime, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was performed as described previously. [31][32][33] Total protein from treated HEC1B and KLE cells was extracted using ice-cold lysis buffer (Beyotime, Shanghai, China). The concentration of the extracted protein was examined using a BCA protein assay kit (Keygentec, Nanjing, China).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…37 Therefore, apoptosis induced by 2 may be a concentrationdependent mechanism; however, more studies are needed to clarify this aspect of its biochemical pharmacology. DAS (4), a fat-soluble compound present in garlic, has demonstrated anticancer activity against hepatocellular, 38 breast, 39−41 skin, 42 and prostate 43 carcinomas. In vivo studies carried out in nude mice injected with human hepatocellular carcinoma (HCC) HepG2 cells and treated with 4 revealed that it inhibited the growth and clonogenicity of HepG2 and Huh7 HCC cells.…”
Section: Natural Allylic Compounds and Cancer Therapymentioning
confidence: 99%
“…It works by activating procaspase-3 to caspase-3 by chelating zinc, as procaspase-3 is known to be inhibited by low levels of this metal. PAC-1 (38) exhibits IC 50 values between 0.003 μM and 1.41 μM in various cancer cells, while the IC 50 values in non-cancerous cells were 7 times higher.…”
Section: Synthetic Allyl Compounds and Their Importance In Cancer The...mentioning
confidence: 99%
See 1 more Smart Citation